Prevalence and Incidence of Drug-Resistant Temporal Lobe Epilepsy in Qatar. (June 2020) - Mesraoua, Boulenouar; Deleu, Dirk; Al Hail, Hassan J; Melikyan, Gayane; Abdalhalim Ali, Musab; Haddad, Naim; Mohamed Ali, Yasir Osman; Elsheikh, Lubna; Ayyad, Ali; Perkins, Jon; Palomo, Gonzalo Alarcon; Asadi-Pooya, Ali A
Background: Information on the epidemiology of temporal lobe epilepsy associated with hippocampal sclerosis (TLE-HS) from Qatar and the developing countries is scarce. To acquire knowledge on the incidence and prevalence of drug-resistant TLE-HS in Qatar, we designed this analytical and extrapolative systematic review of the existing literature. Material and methods: We searched the electronic database PubMed from 1947 until April, 2018, using the following search terms in the title: "epilepsy" OR "temporal lobe" OR "hippocampal sclerosis" AND "epidemiology" OR "incidence" OR "prevalence." Relevant original studies, reviews, and their references, were included. We extrapolated from the previous international literature to estimate the epidemiology of drug-resistant TLE-HS in Qatar. Results: The estimated Qatar incidence of epilepsy varies from 50 to 61 per 100 000 persons per year, and the estimated prevalence of epilepsy is 6.54 per 1000 population; the estimated incidence of TLE varies from 9.5 to 11.6 patients per 100 000 population per year and the estimated prevalence of TLE is 1.76 patients per 1000 people, with 4721 patients having TLE in Qatar. Finally, the reviewed studies also helped in making an estimate of the Qatar prevalence of drug-resistant TLE-HS to be between 0.3 and 0.6 cases per 1000 people (804-1609 current patients) and the Qatar incidence of drug-resistant TLE-HS (2.3-4.3 cases per 100 000 people, per year) with 62 to 116 new patients per year. Conclusion: Our study suggests that 804 to 1609 current patients (with 62-116 additional patients per year) in Qatar are suffering from drug-resistant TLE-HS; emphasis should be placed on the surgical aspect of the current Qatar Comprehensive Epilepsy Program.